Beyond the New Indian History: Recent Trends in the Historiography on the Native Peoples of North America - Rosenthal, Nicolas G. (History compass, 2006)
Since its emergence over thirty years ago, the New Indian history has had a tremendous impact on studies of Native peoples in North America. Nonetheless, in crucial ways and for various reasons, scholarship on American Indians often remains isolated from larger currents of North American history. Just over the last decade, a handful of works have built on the foundations of the New Indian history and more consciously put American Indians into wide ranging conversations about North American culture and society. It is this current wave of scholarship that holds the most promise for moving the study of American Indians beyond the New Indian history and into an even more fruitful period where the connections between the experiences of American Indians and those of other North Americans draw increasing interest and examination.